2013
DOI: 10.1534/genetics.112.147405
|View full text |Cite
|
Sign up to set email alerts
|

Nonself Recognition Through Intermolecular Disulfide Bond Formation of Ribonucleotide Reductase in Neurospora

Abstract: Type I ribonucleotide reductases (RNRs) are conserved across diverse taxa and are essential for the conversion of RNA into DNA precursors. In Neurospora crassa, the large subunit of RNR (UN-24) is unusual in that it also has a nonself recognition function, whereby coexpression of Oak Ridge (OR) and Panama (PA) alleles of un-24 in the same cell leads to growth inhibition and cell death. We show that coexpressing these incompatible alleles of un-24 in N. crassa results in a high molecular weight UN-24 protein co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
(47 reference statements)
0
2
0
2
Order By: Relevance
“…In N. crassa, co-expressing of un-24 OR and un-24 PA results in a weak incompatibility reaction . The N-terminal coding sequence in un-24 is highly conserved and it was shown to not be involved in incompatibility; however, the two morphs are highly divergent in the C-terminus region where incompatibility activity and specificity is localized (Smith et al, 2013). In the tetramer complex, the C-terminus of one large subunit monomer is responsible to reduce the catalytic site of the other large subunit.…”
Section: Het-6 Locusmentioning
confidence: 99%
See 1 more Smart Citation
“…In N. crassa, co-expressing of un-24 OR and un-24 PA results in a weak incompatibility reaction . The N-terminal coding sequence in un-24 is highly conserved and it was shown to not be involved in incompatibility; however, the two morphs are highly divergent in the C-terminus region where incompatibility activity and specificity is localized (Smith et al, 2013). In the tetramer complex, the C-terminus of one large subunit monomer is responsible to reduce the catalytic site of the other large subunit.…”
Section: Het-6 Locusmentioning
confidence: 99%
“…In the tetramer complex, the C-terminus of one large subunit monomer is responsible to reduce the catalytic site of the other large subunit. The model proposed by Smith et al (2013) is that during interaction of the Cterminus and catalytic site, OR and PA forms of UN-24 become covalently linked and inactivated. Interestingly, it has also been found that changing one glutamic acid residue in the C-terminus of UN-24 OR to leucine results in a null allele that is compatible with both OR and PA haplotype (Reshke, 2013).…”
Section: Het-6 Locusmentioning
confidence: 99%
“…Το γονίδιο un-24 κωδικοποιεί για τη μεγάλη υπομονάδα της ριβονουκλεοτιδικής αναγωγάσης τύπου Ι (ribonucleotide reductase, RNR), μιας πρωτεΐνης απαραίτητης για την αντιγραφή του DNA (συγκεκριμένα για τη μετατροπή των πρόδρομων μορίων του RNA σε πρόδρομα μόρια της βιοσύνθεσης του DNA) (Smith et al, 2006). Πρόσφατα προτάθηκε ότι στην ασυμβατότητα που επάγεται από το γονίδιο un-24 εμπλέκεται η δημιουργία ετεροσυμπλόκου των ασύμβατων RNR πρωτεϊνών, η οποία επιτυγχάνεται μέσω διαμοριακών δισουλφιδικών δεσμών (Smith et al, 2013a). Σε άλλη πρόσφατη εργασία αποδείχθηκε πως η ετερόλογη έκφραση του γονιδίου un-24 στον ζυμομύκητα S. cerevisiae σε χαμηλά επίπεδα επάγει έναν φαινότυπο χαρακτηριστικό της HI στους υφομύκητες, ενώ σε υψηλά επίπεδα έκφρασης ο φαινότυπος ασυμβατότητας αναστέλλεται, κάτι που ίσως σχετίζεται με τη λειτουργία πρωτεϊνών θερμικής καταπόνησης (heat-shock protein 70, HSP70) (Smith et al, 2013b).…”
Section: βunclassified
“…αλληλεπιδράσεις (Smith, 2008). Η ποικιλομορφία στον αριθμό των επαναλήψεων WD έχει αποδειχθεί πως συμβάλλει στον καθορισμό της αλληλομορφικής ειδικότητας για τα 3 γονίδια HNWD που έχουν χαρακτηρισθεί μοριακά (het-d, het-e και het-r) (Saupé et al, 1995b, Espagne et al, 19972002;Chevanne et al, 2009).…”
Section: επαγόμενα γονίδιαunclassified